ҚАҲАРМАНЛЫҚ ДӘСТАНЛАРДЫҢ МАЗМУНЫ ҲӘМ КѲРКЕМЛИК СЮЖЕТИНДЕ МИФЛИК МОТИВЛЕР ТИПОЛОГИЯСЫ - Есебаев, М. (SCIENCE and SOCIETY, 2020)
The articale deals with the reasons of occurring of mythical motives in the karakalpak folk eposes. The anthors rereals the typological and artistic familiarities in the plots of the epos.